2019
DOI: 10.25105/jat.v6i2.5495
|View full text |Cite
|
Sign up to set email alerts
|

Kecerdasan Emosional Sebagai Pemoderasi Pengaruh Skeptisme Profesional, Independensi, Time Pressure, Locus of Control Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan

Abstract: <p><em>This objectives of the research to empirically analyze independence, time pressure, and locus of control on the detection of fraud with emotional intelligence as a moderating variable. The population in this study is the auditor who works at the Public Accountant Office in DKI Jakarta in a cluster sampling method, namely the auditor with a minimum of 2 years working experience. Respondents obtained for this study were 154 respondents. Data were analyzed using Moderated Regression.</em>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
2
0
3
Order By: Relevance
“…Thus, time budget pressure has no effect on the auditor's ability to detect fraud. The results of this study are consistent with the results of research which state that time budget pressure does not affect the ability of auditors to detect fraud (Rosiana et al, 2019), (Purba & Nuryatno, 2019). However, this is not in line with other previous results which state that time budget pressure has a negative effect on the ability of auditors to detect fraud (Fadhilah, 2018), (Idawati, 2019), (Arsendy, 2017) Ha4 : Work experience has a positive effect on the auditor's ability to detect fraud ACCEPTED The work experience variable has a sig value of 0.022 (<0.05) states that work experience has a significant positive significant effect on the auditor's ability to detect fraud.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, time budget pressure has no effect on the auditor's ability to detect fraud. The results of this study are consistent with the results of research which state that time budget pressure does not affect the ability of auditors to detect fraud (Rosiana et al, 2019), (Purba & Nuryatno, 2019). However, this is not in line with other previous results which state that time budget pressure has a negative effect on the ability of auditors to detect fraud (Fadhilah, 2018), (Idawati, 2019), (Arsendy, 2017) Ha4 : Work experience has a positive effect on the auditor's ability to detect fraud ACCEPTED The work experience variable has a sig value of 0.022 (<0.05) states that work experience has a significant positive significant effect on the auditor's ability to detect fraud.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed that time budget pressure has a negative effect on the auditor's ability to detect fraud (Fadhilah, 2018), (Idawati, 2019), (Arsendy, 2017). However, the other studies state that time budget pressure has no effect on the auditor's ability to detect fraud (Rosiana et al, 2019), (Purba & Nuryatno, 2019). Based on the description the hypothesis is…”
Section: Time Budget Pressurementioning
confidence: 99%
“…This means that Audit Performance is influenced by Professional Skepticism and Emotional Intelligence. The results of this study are supported by previous research conducted by Sesty (2019) that the Emotional Intelligence variable was not able to moderate the relationship between Professional Skepticism and Audit Performance. Emotional Intelligence only makes an auditor able to control himself and empathize with other parties as well as skilled in establishing good relations with management without assisting the auditor in tracing any audit evidence and related information to improve audit performance.…”
Section:  Emotional Intelligence Moderates the Effect Of Professiona...supporting
confidence: 86%
“…The auditor should not assume that management cannot be trusted, but also should not assume that management's sincerity does not need to be evaluated again. Skepticism does not mean not admitting, but seeking the truth before admitting a statement (Purba, 2019). An auditor must have a skeptical attitude to be able to decide the level of trust and truth in the evidence and information received.…”
Section: Introductionmentioning
confidence: 99%
“…Sehingga, seorang auditor dengan locus of control internal yang tinggi dalam dirinya biasanya mendapatkan peluang lebih besar untuk mendeteksi kecurangan (fraud). Hal ini dibenarkan oleh penelitian yang dilakukan (Purba & Nuryatno, 2019) yang menyatakan locus of control berpengaruh positif terhadap kemampuan auditor mendeteksi kecurangan.…”
Section: Pendahuluanunclassified